Domestic subjective transposition of case in modern Ukrainian language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article focuses on the urgent problems of syntactic transposition theory and functioning of case of noun. Phenomenon case of grammemic transposition in modern Ukrainian literary language studied. The problem of transposition syntactic subjective potential of case and preposition-case forms, principles of classification varieties of transposition have been ascertained.
Keywords: syntactic transposition; domestic transposition of case; case; predicate; subject; sentence